HUBUNGAN PIJAT BAYI TERHADAP KENAIKAN BERAT BADAN PADA BAYI BERAT LAHIR RENDAH (BBLR) : SYSTEMATIC REVIEW - Yustika Ayustira Karim; Martono Tri Utomo; Indra Yuliati (Medika Respati : Jurnal Ilmiah Kesehatan, 2021)
Relationship of Infant Massage to Weight Gains in Low Birth Weight Infant (LBWL): Systematic ReviewBackground: weight gain in LBW infants is very important in preventing an increase in mortality, morbidity, disability and long-term impact on infants. Weight gain is associated with tactile stimulation such as massage. Literally, there have been many studies that have proven the association between infant massage intervention and LBW weight gain, so the researchers conducted a systematic review. Objectives: :  to identify the relationship between infant massage and weight gain in LBW infants. Methods: This study uses a systematic review with the PICOS framework, namely population, intervention, comparators, outcomes, study design and publication type. The research range is from 2011 to 2021 on English-language ProQuest, PubMed, ScienceDirect and ResearchGate searches using full text inclusion criteria using the keywords infant massage, weight gain, infant low birth weight. Results: these results were then screened using the criteria for the year and type of article to produce 253 literatures. The researcher excluded 214 literatures that were not in accordance with the topic or which could not be accessed by full text so that 39 full text literatures were obtained according to the topic. After 39 literatures were reviewed, there were 4 similar literatures, 3 non-English literature, 8 literatures with subjects other than infant low birth weight, 17 literatures that did not examine the relationship between infant massage and weight gain and 3 articles that discussed more than two intervention groups. Finally, there are four literatures analyzed in this systematic review. Assessment of literature quality using EPHPP found that all literature has been indexed by Scopus and is not a predatory journal. Based on data extraction from the four literatures, it was found that baby massage increased changes in infant weight by 619.06 ± 465.23. Conclusion: there is weight gain in infants who are given massage, changes in body weight in infants using massage interventions are higher than infants without massage interventions, and infant massage is associated with weight gain in low birth weight infants.